Applications of Data-driven Models for Daily Discharge Estimation Based on Different Input Combinations - Kumar M.; Elbeltagi A.; Pande C.B.; Ahmed A.N.; Chow M.F.; Pham Q.B.; Kumari A.; Kumar D. (Springer Science and Business Media B.V., 2023)
Decision trees; Errors; Flood control; Floods; Mean square error; Statistical tests; Agriculture management; Burhabalang river; Daily discharge; Data-driven model; Discharge estimation; Flood management; Training and testing; Water flood; Water industries; Water resources management; Rivers; algorithm; error analysis; estimation method; flood control; modeling; river discharge; river flow; India